Tumor type in prediction of survival in patients with endometrial cancer - Dobrzycka, Bożena; Kwiatkowski, Marcin; Kulesza-Brończyk, Bożena; Terlikowski, Sławomir Jerzy (Polish Journal of Public Health, 2011)
Introduction. An ability to predict survival is of crucial importance in determining the need for cancer therapy. Aim. The purpose of this study was to evaluate whether updated tumor type predicts 5-year disease free survival (DFS) for patients with endometrial cancer. Material and methods. Two hundred and eighteen patients who received primary surgical treatment for endometrial cancer were enrolled in this study. The clinical outcomes were compared among the patients with type I and II of endometrial cancer. Results. Among 218 patients in 174 cases were confirmed type I endometrial cancer and in 44 cases were type II. The 5-year DFS of the entire group was 72% in patients with type I tumors and 34% in patients with type II endometrial cancer (p<0.001). The 5-year DFS was 92% for patients with stage I, 70% for patients with stage II and 13% for stage III in type I endometrial cancer compared with 60%, 45% and 0% for those with type II, respectively (p<0.001 and p=0.86, respectively). Tumor grade are the most important factors in type I endometrial cancer and correlated with DFS (p=0.0072). Conclusions. Clinical stage is the most important prognostic factor in type I endometrial cancer. Type II of endometrial cancers is associated with poor prognosis even when at stage I.